On the occurrence and transport of biomass burning haze in south-southeast Asia using observation data and computational methods - Oozeer, Muhammad Yaasiin (2018)
Biomass-burning haze (BBH) is an environmental concern which has a tremendous impact on human health and the economy in Southeast Asia (SEA). One of the worst haze events to ever hit Peninsular Malaysia occurred in June 2013 due to smoke from Riau, Central Sumatra. While biomass-burning in the region is common, the early occurrence of a haze episode of this magnitude is uncharacteristic of the seasonality of extreme fire events which usually occur between August and October in the Maritime Continent (MC). Previous studies on the June 2013 event mostly include statistical studies of the impacts of haze on air quality and health. Therefore, this study aims to investigate the phenomenology of this peculiar haze event and its underlying meteorological forcing agents. The aerosol and meteorological environment during the event is examined using the Moderate Resolution Imaging Spectroradiometer (MODIS) active fire hotspot detections and aerosol optical thickness (AOT) retrievals, satellite based precipitation retrievals and meteorological indices. Particular attention is given to El Niño Southern Oscillation (ENSO) and Madden-Julian Oscillation (MJO) conditions since these phenomena influence inter-annual and intra-seasonal fire-activity, respectively, as well as the influence of tropical cyclones (TC) over the South China Sea. The above datasets are then supported by a WRF-Chem nested simulation to provide a comprehensive picture of the event’s meteorology and aerosol transport phenomenology. Indeed, while the use of weather models to study BBH has become more popular, more modelling efforts need to be put into studying the June 2013 haze event to identify the mechanisms of long range transport of haze.